Abundant pre-industrial carbon detected in Canadian Arctic headwaters: implications for the permafrost carbon feedback. (27th February 2018) - Dean, J F; van der Velde, Y; Garnett, M H; Dinsmore, K J; Baxter, R; Lessels, J S; Smith, P; Street, L E; Subke, J-A; Tetzlaff, D; Washbourne, I; Wookey, P A; et al.
Abstract: Mobilization of soil/sediment organic carbon into inland waters constitutes a substantial, but poorly-constrained, component of the global carbon cycle. Radiocarbon ( 14 C) analysis has proven a valuable tool in tracing the sources and fate of mobilized carbon, but aquatic 14 C studies in permafrost regions rarely detect 'old' carbon (assimilated from the atmosphere into plants and soil prior to AD1950). The emission of greenhouse gases derived from old carbon by aquatic systems may indicate that carbon sequestered prior to AD1950 is being destabilized, thus contributing to the 'permafrost carbon feedback' (PCF). Here, we measure directly the 14 C content of aquatic CO2, alongside dissolved organic carbon, in headwater systems of the western Canadian Arctic—the first such concurrent measurements in the Arctic. Age distribution analysis indicates that the age of mobilized aquatic carbon increased significantly during the 2014 snow-free season as the active layer deepened. This increase in age was more pronounced in DOC, rising from 101–228 years before sampling date (a 120%–125% increase) compared to CO2, which rose from 92–151 years before sampling date (a 59%–63% increase). 'Pre-industrial' aged carbon (assimilated prior to AD1750) comprised 15%–40% of the total aquatic carbon fluxes, demonstrating the prevalence of old carbon to Arctic headwaters. Although the presence of this old carbon is not necessarily indicative of a net positive PCF, we provide an approach and baseline data which can be used for future assessment of the PCF.